Periodic inspection on crop sprayers: Results according to age of sprayers - Antuniassi, Ulisses Rocha [UNESP]; Gandolfo, M. A. (Marcel Dekker Inc, 2005)
The objectives of the IPP Project-Periodic Inspection on Crop Sprayers-are to develop methods for sprayer certification, analyze quality on spray operation, propose an inspection system for crop sprayers in Brazil, improve environmental quality on spray operation, and reduce costs on chemical control for plant protection systems. Periodic inspections on crop sprayers are performed in several countries and are compulsory in most of them, and it is becoming an important tool for improvement and optimization of use of chemicals. The IPP Project in Brazil is funded by FAPESP-Fundação de Amparo a Pesquisa do Estado de São Paulo. The results so far showed that all the sprayers presented failures. However, most of them could be approved with minor services. As an example, 56.6% of the sprayers with more than 2 years of use presented leaks, 47% of them had damaged hoses and 80.5% presented bad tips (nozzles). These results indicate the need for better procedures of use and maintenance of sprayers, justifying the periodic inspection system.
Keywords: sprayers; periodic inspection; application technology; soybean